STATUS GIZI PADA BAYI USIA 6 – 24 BULAN DI WILAYAH KERJA PUSKESMAS KALIBAGOR KABUPATEN BANYUMAS TAHUN 2012 - Tin Utami (Universitas Harapan Bangsa Purwokerto, 2013)
Nutritional status is a state body as a result of food consumption and utilization of nutrients. The purpose of this study was to determine the nutritional status of infantsaged 6-24 months in Puskesmas Kalibagor Banyumas in 2012. Methods This research is descriptive Retrospective Study. Samples were motherswith babies aged 6-24 months with the number of 95 respondents drawn using a randomcluster sampling technique. The results of this study are the nutritional status of infants aged 6-24 months inPuskesmas Kalibagor Banyumas in 2012 mostly in the good category were 83 infants(87.4%). The conclusion in this study that infants aged 6-24 months in the working area ofPuskesmas Kalibagor in 2012 nourished. Keywords: nutritional status of infants aged 6-24 months.